Arctic System Reanalysis improvements in topographically forced winds near Greenland. (19th May 2016) - Moore, G. W. K.; Bromwich, David H.; Wilson, Aaron B.; Renfrew, Ian; Bai, Lesheng
Abstract : Southern Greenland is home to a number of weather systems characterized by high speed low‐level winds that are the result of topographic flow distortion. These systems include tip jets, barrier winds and katabatic flows. Global atmospheric reanalyses have proven to be important tools in furthering our understanding of these systems and their role in the climate system. However, there is evidence that their mesoscale structure may be poorly resolved in these global products. Here output from the regional Arctic System Reanalysis (ASRv1–30 km and ASRv2–15 km grid resolutions) are compared to the global ERA‐Interim Reanalysis (ERA‐I–80 km grid resolution), focusing on their ability to represent winds in the vicinity of southern Greenland. Comparisons are made to observations from surface and upper‐air stations, as well as from research aircraft flights during the Greenland Flow Distortion Experiment (GFDex). The ERA‐I reanalysis has a tendency to underestimate high wind speeds and overestimate low wind speeds, which is reduced in ASRv1 and nearly eliminated in ASRv2. In addition, there is generally a systematic reduction in the root‐mean‐square error between the observed and the reanalysis wind speeds from ERA‐I to ASRv1 to ASRv2, the exception being low‐level marine winds where the correspondence is similar in all reanalyses. Case‐studies reveal that mesoscale spatial features of the wind field are better captured in ASRv2 as compared to the ERA‐I or ASRv1. These results confirm that a horizontal grid size on the order of 15 km is needed to characterize the impact that Greenland's topography has on the regional wind field and climate. However even at this resolution, there are still features of the wind field that are under‐resolved.